INVESTIGATION OF UNWANTED BEHAVIORS OF PRIMARY SCHOOL STUDENTS - Birol ALVER; Fatmanur UĞURLU; Rabia KİNCAL (International Journal of Eurasia Social Sciences, 2018)
The purpose of this study is to examine the unwanted behaviors of primary school students with various variables, based on the views of class teachers. In this study, a semi-structured interview technique, one of the qualitative research techniques, was used. The sample group consists of 789 elementary school students who are educated in Cevdet Samikoglu Primary School in Kagıthane district of İstanbul province in 2017-2018 Spring Semester. 318 (40.3%) were in the second, 204 (5.9%) were in the third, and 267 (33.8%) were studying in the fourth grade of the primary school students participating in the survey. 412 (52.2%) of the students were composed of girls and 377 (47.8%) were composed of males. Interms of overall academic achievement, class teachers assessed 54 (6.8%) students poor, 138 (17.5%) moderate, 194 (24.6%) and 403 (51.1%). According to the opinions of the class teachers, 604 (100%) undesired behaviors observed in the primary school students participating in the research were expressed. According to the frequency of these behaviors: 81 (13.4%) of the low course success; distraction and focus problem 76 (12.5%); withdrawn, withdrawn and silent 66 (10.9%); fighting / violence and being out of order 62 (10.2%); irresponsible behavior and neglect 62 (10.2%); communication-based problems 57 (9.4%); problems based on lack of self-confidence 39 (6.4%); related and adverse affects and problematic behaviors arising from modeling 28 (4.6%); problematic trends from family 27 (4.4%); obsessive behavior 27 (4.4%); compliance problems resulting from foreign nationals 18 (2.9%); selfishness 17 (2.8%); the tendency to lie 13 (2.1%); malnutrition 12 (1.9%); abusive speech 11 (1.8%); jealousy 8 (1.3%).